EU immigration in the British press: How was immigration reported immediately prior to the EU referendum? - Sawsan Askoul (Peoples' Friendship University of Russia (RUDN University), 2018)
This study examines the way in which European Union (EU) immigration was portrayed in the British press during the week immediately prior to the EU referendum of 23rd June, 2016. The research method is based on a combination of corpus linguistics and discourse analysis, with the aim of providing both quantitative and qualitative analysis of the issue. It begins by establishing the rationale behind the proposed topic, before outlining the theoretical and methodological framework of this corpus-based approach to investigating news discourse, which includes the analysis of frequency, concordances and collocates as they occur in three national-wide, online newspapers, namely the Daily Mail, the Guardian and the BBC. Further findings in relation to DA are then discussed, followed by concluding remarks and observations concerning the limitations of this approach and the tool utilised within it.